EFFECTIVENESS OF PREGNANCY EXERCISE ON PAIN REDUCTION AMONG WOMEN IN THE FIRST STAGE OF LABOR - Septa Sari; Dwi Handayani; Pratiwi Puji; Nurhidayah Nurhidayah (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Every woman who gave birth should feel pain during childbirth. One of the ways to reduce labor pain is non-pharmacological method is through pregnancy exercise. From the observations conducted by researchers in March 2016 obtained from 10 nulliparous laboring women, there are three people experiencing mild pain, five people experiencing moderate pain and two people experiencing severe pain during the progress of delivery. Aims: This research aimed to know the differences of the mean level of pain during the first stage of labor between women who performed pregnancy exercise and those who did not. Methods: The design of this research was quasi-experiment. This research conducted in midwive practice Yenni Fitri in Bukittinggi Padang-West Sumatera between March to August 2016. A total of 16 pregnant women and joined the class of pregnant women was selected using purposive sampling method and be asked to fill observation sheet. Results: The result showed that there was a significant different in labor pain during the first stage of labor (p value < 0.001). The mean pain level among pregnant women who participated to pregnancy exercise was 4.03, lower than the control group (6.25). Conclusion: Exercise during the third trimester of pregnancy was the good way to the mother to adapt the pain during delivering baby. Pregnant women can do routine pregnancy exercise from the first trimester of pregnancy. This research is expected to recommend health service providers, especially midwives, to deliver the information and the advantages of pregnancy exercise to the women, and to facilitate exercises on third grade pregnant women since exercise during pregnancy is effective and cost-effective in reducing pain and discomfort during the first stage of labor if done regularly.